A new method to find series solutions of a nonlinear wave equation. (July 2016) - Zhang, Zhi-Yong; Zhang, Wan-Min; Chen, Yu-Fu
Abstract: We show that first-order approximate symmetries of a class of nonlinear wave equations contain Lie symmetries as particular cases. Then we present a new approach to find series solutions of the nonlinear wave equation which cannot be obtained by the standard Lie symmetry and approximate symmetry methods.